The effectiveness and safety of mht depending on the type, route of administration of estrogens, and the type of progestogen. Analysis of data from clinical trials and international recommendations - С. О. Шурпяк (Publishing House TRILIST, 2017)
The hormone therapy remains the most effective method for treating of the vasomotor symptoms and genitourinary syndrome in menopause. The evidence available to date suggests that for women younger than 60 and with a postmenopause no more than 10 years without contraindications, the benefits of administering systemic hormone therapy for the treatment of vasomotor symptoms, sleep disorders and prevention of bone loss exceed possible risks. In addition, the data about statistically significant reduction in all-cause mortality in women who initiate hormone therapy before the age of 60 and/or 10 years after the onset of menopause have been obtained. Menopausal hormone therapy (MHT) includes a wide range of hormonal drugs and administration routes that potentially have different risks and benefits, and therefore the term "class effect" is misleading and inappropriate. The risks of menopausal hormone therapy vary depending on the composition, dose and route of administration of hormones, as well as the timing of the onset and duration of use of both estrogens and progesterone. The use of transdermal estrogens in combination with progesterone seems safer for venous thromboembolism, especially in high-risk women. The use of transdermal estrogen drugs in comparison with oral estrogens is associated with a lesser likelihood of developing thrombotic risk, and possibly the risk of developing stroke and coronary heart disease. If progesterone is needed, micronized progesterone is a safer alternative. MHT requires a periodic reassessment of the benefits and risks for deciding whether to continue or stop using it. The use of postmenopausal hormone therapy in women with menopausal disorders should be based on an assessment of all risk factors for cardiovascular disease, age and time from the onset of menopause. The duration of therapy should be motivated by the indications, and the decision should be taken in conjunction with the doctor.